Pentingnya “Kasih” dalam Surat 1 Yohanes: Tafsiran terhadap Kasih Agape - Reni Marlince Adang; Abad Jaya Zega (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
This article examines the central role and importance of “love” in 1 John, with a particular focus on the concept of agape love. This letter is one of the writings in the New Testament which raises the theme of love in the context of Christians' relationship with God and each other. In this commentary, we explain the meaning, characteristics, and implications of agape love found in 1 John. This research aims to reveal that agape love is not only the foundation of Christian faith, but also plays an important role in shaping the character and ethics of Christian life. We will present key quotes from 1 John that illustrate the message of agape love and discuss how these principles can be applied in contemporary Christian life. The results of this research can provide a deeper understanding of the meaning and value of agape love in the context of this letter and inspire thinking about how to live it in everyday life as a Christian.